Discrimination and Calibration Properties of the Level of Service Inventory–Ontario Revision in a Correctional Mental Health Sample - Olver, Mark E. (Criminal justice and behavior, 2019)
We examined the predictive properties of the Level of Service Inventory-Ontario Revision (LSI-OR) in a sample of 604 provincially incarcerated men with mental illness from a correctional mental health facility followed up nearly 2 years after release. Recidivism base rates and LSI-OR scores were relatively consistent across major mental disorder categories, but higher among individuals with personality disorder, substance use disorder, or dual diagnosis. LSI-OR scores predicted general and violent recidivism in the overall sample and among specific diagnostic groups. Calibration analyses were conducted to model 1-year recidivism estimates for the overall sample and among individual diagnostic groups associated with individual LSI-OR scores. Good correspondence was observed among the different diagnostic groups, with some difference in recidivism trajectories given the differences in base rate. The results support the predictive properties of the LSI-OR with correctional mental health samples and inform the recidivism estimates associated with LSI-OR scores in this population.